Legal Problems on Outdoor Advertising Billboard Tax Collection - Srisubcharoen, Phichayada (Law for Development Graduate Journal, 2024)
The article aims to research the legal measures on outdoor advertising billboard tax collection in Thailand, problems, impacts, and legal measures on the outdoor advertising billboard tax collection of some foreign countries, namely France, Japan, and the United States of America by comparing the legal measures of these countries with the legal measures of Thailand and using them as models for improving Thai legal measures more effective. Based on the study, there are some problems on the Section 6 and Section 7 of Signboard Tax Act B.E. 2510 with unclear scopes and uncorresponding way with principle of tax collection. Therefore, the uncertainty of tax assessment and the legal loopholes occur which being used as the tax avoidance for the taxpayers to pay less or enjoy tax exemption. Furthermore, the tax rates of each type of outdoor advertising billboard are considerably different from another, causing the unfairness or even disputes between the tax officials and taxpayers. These make the outdoor advertising billboard tax collection not as effective as it should be and thus impact the volume of revenue of the local administrative organization. The insufficient revenue caused the local administrative organization to be unable to fully develop its administrative area and provide the public services to the people. For this reason therefore, these should to revised Section 6 and Section 7 of Signboard Tax ACT B.E. 2510. Regarding the provisions, the “outdoor advertising billboards” should have a clearer definition. Also, there should be additional provisions on the type of outdoor advertising billboard taxes and the tax rates in outdoor advertising billboard tax collection. Such improvement might be able to handle the current problematic situation and to prevent the problems in the first place. Besides, to assist the private sector or business owners in paying the outdoor advertising billboards tax correctly and preventing tax avoidance, the effective outdoor advertising billboard tax collection does could financially support the public sectors or local administrative organization. If the provisions still remain unclear, there would be more tax avoidance. Lastly, it is worth noting that the revision will create the better effectiveness and fairness in tax collection to all taxpayers as well.